On effects resulting in appearance of new emission centers at explosive electron emission; Proceedings of the VIIIth International Symposium on Discharge and Electrical Insulation in Vacuum, Albuquerque, september 5-7, 1978 - Mesyats G. A. Gennady Andreyevich (1978, 1978)
В фонде НТБ ТПУ отсутствует